A Wideband Transmitarray Antenna Design Based on the Transmission Characteristic of the UnitCell - Mohammadreza Salimi Beni; Mohammad Zoofaghari (AUT Journal of Electrical Engineering)
In this paper, a procedure is proposed to design a wideband transmitarray upon a specified frequency band. In this way, the phase control parameter of a unit cell is adjusted in a suggested range, ensuring linear phase change and low transmission loss over the band. The unit cell is designed for a range of phase control parameters (e.g., slot length in a CSRR), in which a 360° phase variation is provided. Part of this range is applied for the central elements of TA, in which the maximum overlapped passband (for different values of phase control parameter) around the desired frequency is to be achieved. In this way, a scenario for the phase specification of the array elements would be obtained. This range is specially applied for the central elements of the array, which are in exposure to feed peak power. As a proof of this concept, a 14×14 element transmitarray is designed and fabricated based on a back-to[1]back square Complementary Split-Ring Resonator (CSRR). Measurement results indicate maximum gain, 1-dB bandwidth, and aperture efficiency of 24.6 dB, 18.4%, and 53% respectively, at the center frequency of 11.5GHz. At the end of the paper, a comparison between the proposed TA and the previous ones is provided.